The impact of organizational structure on the social responsibility of companies in the energy sector - Stevanović Marija; Jovanović Violeta; Simonović Danijela; Krstić Vesna (Bakar)
The driver of modern world industry is electricity. Production, distribution and use of electricity affect the functioning of modern industrial plants, the process of communication in the modern world, as well as numerous other types of services that are necessary for people's lives. The technological process of coal-based electricity production contributes to the increased emission of gases that have a large negative impact on the environment. Carbon dioxide (CO2 ), sulfur dioxide (SO2 ), nitrogen oxides (NOx ), carbon monoxide (CO) and solid PM particles are the main constituents of polluting gases from thermal power plants. All the mentioned compounds have harmful effects on the environment, and in the long term they also affect climate change (greenhouse effect). Due to the aforementioned problems, it is important to apply the principles of corporate social responsibility to companies in the energy sector. The aim of the paper is to evaluate the impact of the organizational structure of the company on the development of the system of corporate social responsibility in companies from the energy sector. The research results confirmed the positive impact of the organizational structure on socially responsible business practices